Tracing Digital Traces of Money Laundering in Order to Restore State Losses in the Perspective of Justice - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2024)
Current media facilities and internet networks, people can receive and disseminate information through digital media. Rapid the development of technology and communication has consequences that have an impact on changes in patterns of production and consumption of information carried out by the general public. So researchers are interested in doing this in order to increase vigilance in conducting transactions and data privacy so that can reduce criminal acts related to data or cybercrime. The results showed that in this digital era, the function of the library as information and knowledge service providers change. Library must change the paradigm to be more technology-based and develop themselves, so that as a source of library learning remains a bone backs of the nation in gaining knowledge and deepening scientific, The dynamics of money laundering is growing rapidly is the reason, so it is appropriate in the search for money laundering must use credible digital technology.